The unseen archive of Idi Amin photographs from the Uganda Broadcasting Corporation - Derek R. Peterson and Richard Vokes (Munich ; New York Prestel, 2021)
Chosen from a collection of 70,000 negatives from the archive of the Uganda Broadcasting Corporation, the images in this remarkable collection were taken by Amin's personal photographers between the 1950s and mid-1980s. Like many dictators, Amin used photography as a means of spreading propaganda that would flatter his regime while obscuring its failures and abuses. Organized into thematic sections, these photographs show how Amin sought to gain support for acts such as his expulsion of tens of thousands of South Asians in 1972 and for the "Economic War," in which citizens charged with petty theft were tried and executed. There are also fascinating insights into the ways Amin hoped to promote Ugandan arts and culture, including a food-eating competition in Kampala and ceremonial visits to
Includes bibliographical references.
Keywords: Amin, Idi, 1925-2003.